Histopathologic features of the spontaneous pustular lesions of Behcet's syndrome - ERGUN, SAFİYE ATLAS TÜLİN (WILEY-BLACKWELL, 1998)
Background Papulopustular lesions are common in Behcetls syndrome (BS), A debate exists as to whether they are different from ordinary acne, This has important clinical and pathophysiologic implications. Objective The aim of this study was to evaluate the histopathologic features of papulopustular lesions seen both in BS and acne vulgaris (AV). Methods Representative samples were obtained from 17 patients with BS and six patients with AV. The detailed histopathologic features were evaluated by a dermatopathologist blinded to the diagnoses. Results Considering the epidermis, follicle epithelium, and dermis separately, no differences could be found between the two groups. Conclusions The papulopustular lesions seen in these two disorders cannot be distinguished on the basis of clinical and histopathologic findings.